Pengembangan dan Analisis Umkm Keripik Pisang di Desa Kertosuko - Jupri, Moh.; Fauzan , Ahmad (Najah: Journal of Research and Community Service, 2026)
Real Work Lecture (KKN) is a special form of community service activity, because in KKN darma education and teaching, research and community service are integrated into it and involve a number of students and a number of teaching staff plus members of the community. Banana and cassava chips are chips made from processed bananas are fried in the usual way, namely by using a cauldron or frying pan. Kertosuko Village is one of the villages located in the administrative area of ​​Krucil District, Probolinggo Regency with the western boundary bordering Betek Village, east bordering Bondowoso Regency, north bordering Tambelang Village and to the south by Segaran Village. The method used by researchers is observation and interviews. Based on the results of an evaluation of food labeling at Ms. Arifin's MSMEs that are not in accordance with the packaging, it is necessary to make improvements related to product packaging.